Determination of columnar amounts of atmospheric minor constituents from measurements of infrared solar spectra: Antarctic MAP - Yukio Makino; Masataka Shiobara; Hisafumi Muramatsu; Sadao Kawaguchi; Takashi Yamanouchi; Masayuki Tanaka; Toshihiro Ogawa; Koji Masutani; Masao Morii (National Institute of Polar Research, 1985)
As part of the Japanese Antarctic Middle Atmosphere Program (Antarctic MAP), columnar amounts of atmospheric minor constituents such as N_2O, CH_4,CFCl_3,CF_2Cl_2 and HNO_3 were determined from measurements of infrared solar spectra for the period 24 March 1983-29 December 1984 at Syowa Station, Antarctica (69°00′S, 39°35′E). A Fourier-transform-infrared spectrometer was used to measure the solar spectra. The highest apodized resolution of the spectrometer is 0.1(cm)^ (full width at half-maximum), but the resolution of 0.8(cm)^ was adopted in routine operation because of an economy of data processing time and of better signal to noise (S/N) ratio. The accuracy of measurements is estimated from S/N ratios of the obtained spectra; typical errors of measured abundances were ±40,±2 and ±6% for CFCl_3 (at 850(cm)^), N_2O (at 2576(cm)^) and CH_4 (at 6004(cm)^), respectively. A MCT detector (cooled at 77 K) is desirable to attain higher resolutions (∿0.1(cm)^) and larger S/N ratios.